Simulation and Experimental Analysis of Mass Transfer in a Liquid-Liquid Stirred Tank Extractor - 안병성; 이원국 (AMER CHEMICAL SOC, 1990)
Mass transfer in liquid-liquid dispersion in a stirred tank has been investigated experimentally for several particular cases. Since the mass-transfer resistance inside a drop depends on the internal circulation condition, the mass-transfer rate can be predicted from the modified rigid sphere model with the internal circulation correlation factor, R. Experimental results show that R is nearly 1, which means that drops are internally stagnant in a stirred tank extractor within the experimental ranges. The ratio of the resistances of the dispersed and the continuous phases is obtained from the proposed equations that are proven to be applicable to calculate the mass-transfer coefficients in a stirred tank extractor. The limit conditions in which one of the resistances of the two phases can be ignored are fully discussed. Extraction efficiencies and drop size distributions for the various experimental conditions are predicted, and they are well fitted with those obtained from experiments. ？ 1990, American Chemical Society. All rights reserved.